2005
DOI: 10.1520/jai12977
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Additive Chemistry and Its Effects on the Phosphorus Volatility of Engine Oils

Abstract: The most widely used and effective anti-wear/anti-oxidation additives in engine oil contain phosphorus that can partially volatilize during engine operation. Unfortunately, volatile phosphorus in the exhaust stream degrades the function of the exhaust catalyst in reducing air pollution. Earlier studies in a special volatility bench test using the Phosphorus Emission Index have shown that phosphorus volatility is not related to engine oil volatility or to phosphorus content in the unused engine oil. At the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Current interest in ZDDP has included such topics as ligand exchange, [3,4] oxidation inhibition, [5] thermal film formation, [6] tribofilm formation, [7] antiwear properties, [8,9] friction properties, [10 -12] and interaction with other lubricating oil components. [13] Because of the need to replace ZDDPs partially or wholly by other phosphorus-free additives, [14] there is considerable interest in better understanding the chemistry of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Current interest in ZDDP has included such topics as ligand exchange, [3,4] oxidation inhibition, [5] thermal film formation, [6] tribofilm formation, [7] antiwear properties, [8,9] friction properties, [10 -12] and interaction with other lubricating oil components. [13] Because of the need to replace ZDDPs partially or wholly by other phosphorus-free additives, [14] there is considerable interest in better understanding the chemistry of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…Small samples of the original oils and the volatile materials and residues obtained during the Selby-Noack tests in the associated paper [1] were analyzed by 31 P NMR at Washington University (St. Louis, MO). The spectra were obtained either on a 500 MHz Varian NMR equipped with a 10 mm probe or on a 600 MHz Varian NMR equipped with a 5 mm probe.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the main elements of the lubrication oil were calcium (Ca, 1710 mg kg −1 ), zinc (Zn, 1300 mg kg −1 ), and phosphorus (P, 1230 mg kg −1 , Table S6). These are typical additives used in lubrication oil (Selby et al 2005;Lin et al 2015). Ca is commonly used as a detergent additive, while Zn and P are used as extreme pressure-additives as well as wear protection additives (Selby et al 2005;Lin et al 2015).…”
Section: Fuelsmentioning
confidence: 99%
“…These are typical additives used in lubrication oil (Selby et al 2005;Lin et al 2015). Ca is commonly used as a detergent additive, while Zn and P are used as extreme pressure-additives as well as wear protection additives (Selby et al 2005;Lin et al 2015). Other abundant elements found in the lubrication oil were boron (B, 310 mg kg −1 ), followed by sodium (Na, 47.6 mg kg −1 ), silver (Ag, 11.6 mg kg −1 ), magnesium (Mg, 8.9 mg kg −1 ), potassium (K, 8.1 mg kg −1 ), copper (Cu, 6.8 mg kg −1 ), and silicon (Si, 5.0 mg kg −1 ) (Table S15).…”
Section: Fuelsmentioning
confidence: 99%